Reducing the risk of iatrogenic Creutzfeldt–Jakob disease by improving the cleaning of neurosurgical instruments. Issue 3 (November 2018) - Smith, A.; Winter, S.; Lappin, D.; Sherriff, A.; McIvor, I.; Philp, P.; Suttner, N.; Holmes, S.; Stewart, A.
Summary: Background: In all, there have been 178 variant Creutzfeldt–Jakob disease (vCJD) patients diagnosed in the UK, with an estimated maximum 1:2000 carriage rate based on archived appendix and tonsil tissue, implying that infection may be rare but carriage relatively frequent. Previous workers have identified that maintenance of surgical instruments in a humid atmosphere after use and prior to cleaning assists cleaning efficacy. Recently the Department of Health/Advisory Committee on Dangerous Pathogens UK have recommended a surgical instrument cleanliness threshold post cleaning of <5 μg protein per instrument side. Aim: To quantify cleanliness of neurosurgical instruments and to investigate cost-effective measures for improved cleaning. Methods: Two instrument protein quantification methods were used: one based on the International Standard (15883 series) using sodium dodecyl sulphate elution and ortho -phthalaldehyde reaction, and a second in-situ protein fluorescence detection system (ProReveal) providing results per instrument side. In-vitro investigation of the efficacy of some commercial and in-house pre-clean wetting agents was undertaken using artificial test soil and stainless steel discs under standard conditions. In-vivo evaluation of best-performing in-vitro agents was undertaken on craniotomy sets. Findings: ProReveal technology demonstrated that 163 out of 187 (87%) neurosurgical instruments had <5 μg residual protein per instrument side. The use of proprietary National Health Service plastic bags and sterile water-soaked wound pads were equivalent in efficacy to commercial pre-cleaning wetting products and significantly less expensive. Conclusion: Although we demonstrate low in-situ protein levels on neurosurgical instruments and the beneficial effects of keeping instruments moist, other cleaning critical-control points such as instrument loading patterns should also be monitored.